Pendidikan Islam Menyikapi Punishment Anak (Studi Literatur) - Mohammad Wisnu Khumaidi; Muhammad Ari Wibowo (Program Studi Pendidikan Agama Islam, 2024)
Islam has regulated how to punish children when they make mistakes, namely: First, the basis for treating children is in a gentle and loving way, as stated in the following Hadith: Al-Bukhari stated in Al-Adabul Mufrad,